The Role Of Laz As A Zakat Manager In Productive Zakat Use: Case Study Of Rumah Zakat Medan - Sri Wahyuni (Program Pascasarjana UIN Sumatera Utara Medan, 2017)
Productive utilization of zakat by the Zakat Collection Institution (LAZ) will bring in benefit for The establishment of Islamic principles and the enhancement of the socio-economic resources of the Muslim community in Indonesia. The productive utilization of ZIS is in line with Islamic principles that aim to achieve the welfare of the community. Moreover, this has been regulated (legislated) by the government. Rumah Zakat is one of the Zakat Collection Institutions (LAZ) that has obtained a permit and is in accordance with Article 18 of Law Number 23 of 2011 concerning Zakat Management. This institution has attempted to distribute zakat in a non-consumptive manner, namely by giving it directly to eight asnaf without being utilized so that the zakat is used up and there is nothing left. This zakat house has tried to distribute zakat in a productive way, including by providing zakat in the form of capital loans in the form of independent community businesses in the form of charity loans. The utilization of productive zakat carried out by the zakat house motivated the author to conduct more intensive research to see how the law of productive zakat, whether providing capital for independent businesses from zakat assets to mustahik is justified in sharia, whether in the utilization of productive zakat there are obstacles faced by the zakat house.